Single-Camera Computer Vision Algorithm for Robot Shortest Path Estimator using morphological structuring element with variable sizes - Hasan, Sami; Th.Yousir, Naeem; S. Jumaa, Shereen (International Journal of Engineering and Technology, 2018)
The robotic challeng of developing and implementing aÂ shortest-path finding algorithm to reach a destination without bumping intoÂ obstacles has been tackled in thisÂ paper. The proposed algorithm is utilized a single ceiling fixed camera and based on the mask and robot size with different sizes for dilation mask. The implementation has been successfully produced thirty-three computer vision figures and two comparison tables of simulation results by using morphological structuring element with different sizes. This paperâ€™s proposal of optimal path finding algorithm is effeciently save robot energy in reaching targets.Â Â Â